An analysis of China's grain production: looking back and looking forward. (9th December 2013) - Li, Yuxuan; Zhang, Weifeng; Ma, Lin; Wu, Liang; Shen, Jianbo; Davies, William J.; Oenema, Oene; Zhang, Fusuo; Dou, Zhengxia
Abstract Ensuring food security is the foundation of economic development and social stability. China is historically a country that is dominated by agriculture. In the past 60 years, China's total grain output increased by fivefold, from 113 million tons (MT) in 1949 to 571 MT in 2011, a statistic which provides inspiration to producers in other parts of the world. Grain production per capita doubled, from 209 to 425 kg during the same time period. At the national scale, China has succeeded in maintaining a basic self‐sufficiency for grain for the past three decades. However, with the increasing population pressure and a growing appetite for animal products, China will need 776 MT grain by 2030 to feed its own people, a net increase of 35.9% from its best year on record. China's drive for future food security is challenged by problems such as low efficiency of resource use and resource limitation, diminishing return in yield response, competition for nonagricultural land uses, and environmental degradation. In this article, we analyze historical, temporal, and spatial variation in total grain production as well as the overall developing trends of current and future grain production, and discussed relevant options to overcome production constraints and further promote agricultural production.